Rice market liberalization and poverty in Viet Nam - Minot, Nicholas; Goletti, Francesco (International Food Policy Research Institute, 2000)
Market liberalization, though an important element in economic reforms in developing countries in the past two decades, has been accused of harming the poor through higher food prices, layoffs in formerly state-owned enterprises, and the erosion of social safety net programs. Since the 1980s Viet Nam has relaxed a number of government controls over rice production and marketing, stimulating large increases in rice production. Yet the government retains control over rice exports and internal rice trade. Rice Market Liberalization and Poverty in Viet Nam, Research Report 114, analyzes whether further loosening of state controls in Viet Nam’s rice markets would help or hurt the poor and draws lessons for other countries.